2007
DOI: 10.4049/jimmunol.178.2.1151
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 and IDO Expression by Human Gingival Fibroblasts via TLRs

Abstract: Human gingival fibroblasts (HGFs), a predominant cell type in tooth-supporting structure, are presently recognized for their active role in the innate immune response. They produce a variety of inflammatory cytokines in response to microbial components such as LPS from the key periodontal pathogen, Porphyromonas gingivalis. In this study, we demonstrated that HGFs expressed mRNA of TLRs 1, 2, 3, 4, 5, 6, and 9, but not TLRs 7, 8, and 10. Stimulation of HGFs with highly purified TLR2 ligand (P. gingivalis LPS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
1
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 54 publications
6
104
1
11
Order By: Relevance
“…IDO expression is induced mainly by IFNs and LPS in cells from various organs and within tissue-invading cells during inflammation (4,15,16). IDO activity of APCs, epithelial cells, fibroblasts, or tumor cells has been demonstrated to block T cell responses toward allogeneic fetuses, grafts, and tumors, and may play a role in the prevention of allergic disease (17)(18)(19)(20)(21)(22)(23)(24). Downstream metabolites of Trp, which are produced by IDO activity in murine DCs, are able to convert otherwise immunogenic and IDO-incompetent murine DCs into tolerizing DCs (25).…”
mentioning
confidence: 99%
“…IDO expression is induced mainly by IFNs and LPS in cells from various organs and within tissue-invading cells during inflammation (4,15,16). IDO activity of APCs, epithelial cells, fibroblasts, or tumor cells has been demonstrated to block T cell responses toward allogeneic fetuses, grafts, and tumors, and may play a role in the prevention of allergic disease (17)(18)(19)(20)(21)(22)(23)(24). Downstream metabolites of Trp, which are produced by IDO activity in murine DCs, are able to convert otherwise immunogenic and IDO-incompetent murine DCs into tolerizing DCs (25).…”
mentioning
confidence: 99%
“…Recently, Mohanonda and colleagues reported that the TLR-2, TLR-3, TLR-4 and TLR-5 ligands enhanced IL-8 production from HGF, although the TLR-9 ligand did not [14]. Moreover, they reported that the TLR-9 ligand suppressed IL-8 production from TLR-3 ligand-stimulated HGF [14].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Mohanonda and colleagues reported that the TLR-2, TLR-3, TLR-4 and TLR-5 ligands enhanced IL-8 production from HGF, although the TLR-9 ligand did not [14]. Moreover, they reported that the TLR-9 ligand suppressed IL-8 production from TLR-3 ligand-stimulated HGF [14]. Their report may explain why the TLR-9 ligand It is reported that both T helper type 1 (Th1) and Th2 cells exist in periodontally diseased tissues [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HGFs have previously been reported to express the genes for Toll-like receptors (TLR) 1-5 and 9, which are widely known as receptors for pathogens; in particular, TLR-2,3,4 and 5 have been reported to be specifically involved in the expression of IL8 24) , and TLR-2 is known to be involved in the expression of IL-6 25) . These results support the fi nding of enhanced production of these cytokines following pathogen stimulation.…”
Section: Discussionmentioning
confidence: 99%